POPULATION STRUCTURE AND PRODUCTION PERFORMANCE OF ASEEL PARENT POPULATION IN TIRUPPUR DISTRICT OF TAMIL NADU - N. Murali; M. Malarmathi; R. Richard Churchil (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A survey was conducted to assess the breeder production performance in Aseel breeding farms. Aseel birds had multicolored plumage with solid feather patterns distributed all over the body. Pea combs, strawberry and single comb were observed in the population. Birds were housed in layer shed with the ratio 1 male for 8 female. Age at first egg was recorded as 139±1.94 days. Average cumulative egg production up to 120 weeks per bird was 160.59±0.59 with the 77% hatchability. Percentage hen day egg production for Aseel was 29.72±1.60 and the effective population size (Ne) ranged from 352.94 to 4781.16 and the overall mean Ne in the Aseel population was 2086.59±148.35 with the rate of inbreeding 0.0003.